The VFH1 (YLL056C) promoter is vanillin‐inducible and enables mRNA translation despite pronounced translation repression caused by severe vanillin stress in Saccharomyces cerevisiae. Issue 7 (7th May 2018) - Nguyen, Trinh Thi My; Ishida, Yoko; Kato, Sae; Iwaki, Aya; Izawa, Shingo
Abstract: Vanillin, furfural and 5‐hydroxymethylfurfural (HMF) are representative fermentation inhibitors generated during the pretreatment process of lignocellulosic biomass in bioethanol production. These biomass conversion inhibitors, particularly vanillin, are known to repress translation activity in Saccharomyces cerevisiae . We have reported that the mRNAs of ADH7 and BDH2 were efficiently translated under severe vanillin stress despite marked repression of overall protein synthesis. In this study, we found that expression of VFH1 ( YLL056C ) was also significantly induced at the protein level by severe vanillin stress. Additionally, we demonstrated that the VFH1 promoter enabled the protein synthesis of other genes including GFP and ALD6 under severe vanillin stress. It is known that transcriptional activation of VFH1 is induced by furfural and HMF, and we verified that Vfh1 protein synthesis was also induced by furfural and HMF. The null mutant of VFH1 delayed growth in the presence of vanillin, furfural and HMF, indicating the importance of Vfh1 for sufficient tolerance against these inhibitors. The protein levels of Vfh1 induced by the inhibitors tested were markedly higher than those of Adh7 and Bdh2, suggesting the superior utility of the VFH1 promoter over the ADH7 or BDH2 promoter for breeding optimized yeast strains for bioethanol production from lignocellulosic biomass.